"Matter of climate change" or "Matter of rapid urbanization"? Young people's concerns for the present and future urban water resources in Ho Chi Minh City metropolitan area, Vietnam. (April 2023) - Nguyen, Thi Phuoc Lai; Virdis, Salvatore G.P.; Vu, Thanh Bien
Abstract: Through an integrated empirical study in the Ho Chi Minh City metropolitan, we examined the effects of urban land use and climate change on water management, as well as young people's concerns about the issue. The results showed that between 1992 and 2019, the population increased from 3, 272, 000 to 8, 993, 082 residents, while urban settlements increased from 288 km 2 to 958 km 2, with a higher rate observed after the year 2000. Climatic analysis showed an average temperature increasing trend of about +0.27 °C/decade, with a significant increase up to +0.34 °C/decade observed after the year 2000, while precipitation did not show a significant trend. The study revealed young people perceived great changes in urban water bodies - polluted and encroached on by infrastructure over the last decades, and believed climate is changing, which poses risks to humans. The youth's perceptual experiences and beliefs are symmetric with the monitoring data. They are also concerned about future urban water resources. The Partial Least Square Structural Equation Modelling showed these concerns were shaped by the perceptual experience of rapid urbanization rather than climate change belief. The finding appeals to a holistic alternative for urban water management by improving the connections and integration with urban planning. Graphical abstract: Image 1 Highlights: Urbanization and population growth showed a very strong positive correlation. Urban areas and temperature increased at a faster pace after the year 2000. Symmetry found between young people's urbanization experiences and CC beliefs. Young people are concerned about the present and future urban water resources. Young people's concerns are associated with the "matter of urbanization".